Distribution of plasminogen activator inhibitor in normal liver, cirrhotic liver, and liver with metastases. Issue 3 (March 1994) - Fitch, P; Bennett, B; Booth, N A; Croll, A; Ewen, S W
Abstract : AIMS–To examine the distribution of PAI-1 antigen in normal and cirrhotic liver and liver with metastases. METHODS–Sections of normal and cirrhotic liver and liver with metastases were stained using the alkaline phosphatase antialkaline phosphatase (APAAP) technique and monoclonal antibody specific for plasminogen activator inhibitor (PAI-1). RESULTS–PAI-1 antigen was identified as discrete granules in the cytoplasm of hepatocytes in normal liver, particularly around portal tracts and central veins of the liver lobule. In cirrhotic liver a striking reduction of PAI-1 antigen was noted. In liver with metastases increased amounts of PAI-1 antigen were concentrated in hepatocytes around the margins of malignant deposits. CONCLUSIONS–Cirrhotic liver contains considerably less PAI-1 antigen than does normal liver, despite raised plasma concentrations of PAI-1. This may reflect release of hepatic PAI-1 into the circulation or decreased clearance of PAI-1 from the plasma. Secondary malignant deposits in the liver seem to stimulate production of PAI-1 in adjacent hepatocytes. This may influence the invasive process and may contribute to the thrombotic tendency associated with malignancy.